(The Production of Fresh and Healthy Sugar Cane Juice) - M.S., Zarlis (Balai Besar Industri Agro, 2010)
Research on the production of fresh and healthy sugar cane been conducted. the purpose of this study is to find out such of the simple technology which can be used for additional materials that wealthy to pure impurities of sugar cane, in order to produced special sugar cane juice, natural color, most of the consumers like to, and keeping for a long time. the implementation of this research by giving additional ascorbic acid :0%, 0,05%, 0,10%, and 0,15%, egg albumin floculant (2 eggs for each sugar cane juice per liter); sterilization at 70oC, filtration, pasterurilization at 121oC during 5 minutes, storage in room and cold chamber temperature. The result of the optimal research shows that the process of this study which gives 0,10% ascorbic acid as the additional assence, bright yellowish color, specific taste of fresh sugar cane that to be fond of panelist; pH 5.11; ascorbic acid content 51.8 mg/100 ml; sugar content 16.6%; turbidity 11.08 FTV; color 8,07 Pt. Co; metals pollution (Pb,Cu and Zn) with microbiologis pollution (ALT,coliform and yeast/mold) are fulfill the standard grade of drink. It,s still in good and worthy for more than one (1) year in the cold chamber/refrigerator and of course 2.5 months in the room storage.The implementation of this research can be aplicated in the small scale of industry.